2015
DOI: 10.3390/ma8063562
|View full text |Cite
|
Sign up to set email alerts
|

A New Predictive Model of Centerline Segregation in Continuous Cast Steel Slabs by Using Multivariate Adaptive Regression Splines Approach

Abstract: The aim of this study was to obtain a predictive model able to perform an early detection of central segregation severity in continuous cast steel slabs. Segregation in steel cast products is an internal defect that can be very harmful when slabs are rolled in heavy plate mills. In this research work, the central segregation was studied with success using the data mining methodology based on multivariate adaptive regression splines (MARS) technique. For this purpose, the most important physical-chemical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…where MSRE denotes the mean squared residual error and M(λ) is the complexity level of the MARS model given by the number of BFs included in the model (adding its corresponding intercept term) as well as the parameter d, known as the "penalty of the model". Since this parameter can also be considered as a smoothing parameter [122] and in this research the value d = 2 was employed to configure a pairwise interactive analysis model [95,99,104,107], the complexity is equal to:…”
Section: Synopsis Of the Mars Methodologymentioning
confidence: 99%
“…where MSRE denotes the mean squared residual error and M(λ) is the complexity level of the MARS model given by the number of BFs included in the model (adding its corresponding intercept term) as well as the parameter d, known as the "penalty of the model". Since this parameter can also be considered as a smoothing parameter [122] and in this research the value d = 2 was employed to configure a pairwise interactive analysis model [95,99,104,107], the complexity is equal to:…”
Section: Synopsis Of the Mars Methodologymentioning
confidence: 99%
“…Singla et al [26] used the factorial design for investigating the effect of cerium oxide addition on the dry sliding adhesive wear behavior of hardfaced Fe-18Cr-1.1Nb-2.1C alloy and a regression equation of the model was developed and validated with experimental tests. García Nieto et al [34] used multivariate regression to predict the segregation in continuous cast steel slabs and the results allowed to determinate the most important variables that impact in the industrial process directly.…”
Section: Introductionmentioning
confidence: 99%
“…When we consider the multivariate statistics applied to the context of steelmaking processes, studies can be found for the calculation of the mass balance of blast furnaces (Ruuska, Sorsa, Lilja & Leiviskä, 2017), estimation of the energy conservation potential in the Chinese industry (Rao, Rama, Subbaiah, Rao & Rao, 2013), early detection of segregation in continuous casting processes (Nieto et al, 2015), among others. We can also point out the use of different application methods for the analysis of multivariate statistics in steel processes, such as logistic regression in (Xu & Zhao, 2005), and robust regression methods (Mondal, 2016), for example.…”
Section: Multivariate Statistics In Steelmaking Processmentioning
confidence: 99%